A comparison study of face stability between the entering and exiting a shallow-buried tunnel with a front slope - Li, Xinzhe; Li, Xiulei; Yang, Chao (Frontiers in Earth Science, 2022)
Worldwide, it is a great challenge to tunnel in portal section, where excessive deformation, cracking, or even collapse often occurs during the construction process. This paper presents a comparison study of face stability between entering and exiting a shallow-buried tunnel with a front slope. Firstly, the theoretical solutions of support pressure T and safety coefficient FS of the excavation face considering surface slope are derived by upper-bound limit analysis method. Secondly, for different slope angles, buried depth and surrounding rocks of the exit and entrance sections, the T and FS are obtained. The results show that when the burial depth of the tunnel crown h remain constant, the T increased first and then decreased while the FS increased gradually, and both become steady when the slope angle  arrive at a certain value. In addition, the thicker the h is, the smaller the certain value  is. When the h and  remain constant, the loose area in front of the excavate face will decreased apparently with the increase of the internal friction angle , thus the T will decrease and FS will increase. Moreover, the T decreased linearly with the increase of cohesion c and unit weigh of surrounding rock, while the FS is the opposite. Compared with the entrance section, the construction risk at the exit section is greater.